Advances in soft computing : 18th Mexican International Conference on Artificial Intelligence, MICAI 2019, Xalapa, Mexico, October 27 - November 2, 2019, Proceedings : Preface - Martinez-Villaseñor, Lourdes (Springer, 2019)
The Mexican International Conference on Artificial Intelligence (MICAI) is a yearly international conference series that has been organized by the Mexican Society of Artificial Intelligence (SMIA) since 2000. MICAI is a major international artificial intelligence (AI) forum and the main event in the academic life of the country’s growing AI community. The proceedings of MICAI 2019 contains 59 papers structured into four sections: Machine Learning, Fuzzy Systems, Reasoning, and Intelligent Applications, Computer Vision and Robotics, Optimization and Planning This book should be of interest to researchers in all fields of AI, students specializing in related topics, and for the public in general interested in recent developments in AI. ©Springer Nature Switzerland AG 2019.
Advances in soft computing : Preface
Preface : Advances in soft computing : 18th Mexican International Conference on Artificial Intelligence, MICAI 2019, Xalapa, Mexico, October 27 - November 2, 2019, Proceedings